Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 7 - Section 7.1 - Simplifying Rational Expressions - Exercise Set: 52

Answer

$\dfrac{49-y^{2}}{y-7}=-y-7$

Work Step by Step

$\dfrac{49-y^{2}}{y-7}$ Factor the numerator: $\dfrac{49-y^{2}}{y-7}=\dfrac{(7-y)(7+y)}{y-7}=...$ Change the sign of the denominator. To do so, also change the sign of the fraction. After that, simplify: $...=-\dfrac{(7-y)(7+y)}{7-y}=-(7+y)=-y-7$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.